The difference of paraspinal muscle between patients with lumbar spinal stenosis and normal middle-aged and elderly people, studying by propensity score matching - Wang, Wei; Guo, Yang; Li, Weishi; Chen, Zhongqiang (Frontiers in Endocrinology, 2022)
Objective: The purpose of this study was to elaborate the characteristics of paraspinal muscles in lower lumbar, to compare the differences of paraspinal muscle between patients with lumbar spinal stenosis and normal people and to explore the influencing factors of paraspinal muscle degeneration in patients with lumbar spinal stenosis. Method: The 39 pairs of patients and normal people were selected by propensity score matching. The differences of multifidus muscle and erection spine muscle parameters between the two groups were compared by independent-samples t-test and the relationship between age, paraspinal muscle degeneration and other factors in patients with lumbar spinal stenosis was analyzed by Pearson or Spearman correlation analysis. Result: The general conditions of the two groups (patients with lumbar spinal stenosis and normal people) were well matched. There were significant differences in the relative fatty cross sectional area, fatty infiltration and relative signal intensity of multifidus muscle at L3 level. The fatty infiltration and relative signal intensity of multifidus muscle at L4 level and the relative signal intensity of multifidus muscle at L5 level were also significantly different. For male, the relative fatty cross sectional area, the fatty infiltration and relative signal intensity of multifidus muscle in patients were higher than those in healthy peers. For female, the relative signal intensity of multifidus muscle in patients was higher, too. In patients group, age was significantly correlated with the relative fatty cross sectional area, fatty infiltration and relative signal intensity of multifidus muscle and erector spine muscle. Weight and BMI were significantly correlated with the relative total cross-sectional area of erector spinal muscle. The fatty infiltration increased more significantly with age in patients than that in normal people. Conclusion: The change rules of paraspinal muscles in patients with lumbar spinal stenosis are similar to those in normal people. The degeneration of paraspinal muscle in patients with lumbar spinal stenosis was more severe than that in normal people, mostly in multifidus muscle. The paraspinal muscle degeneration was related to age in patients, and the effect of age on atrophy of paraspinal muscle was greater than that of normal people.